A Psychological Analysis of Students' Self-Efficacy in Learning: A Comparative Study between Indonesian and Egyptian High School Students - syafii, hisyam; Azhari, Husain (Indonesian Journal of Islamic Educational Review, 2025)
Academic self-efficacy plays a critical role in shaping students' academic performance and resilience. This study aims to compare the academic self-efficacy of high school students in Indonesia and Egypt, focusing on how contextual factors such as education systems and cultural norms influence this psychological construct. A quantitative cross-country comparative method was employed, involving 100 students (50 from Yogyakarta, Indonesia, and 50 from Cairo, Egypt) selected using proportional stratified random sampling. Data were collected using the Academic Self-Efficacy Scale, validated for cross-cultural contexts, and analyzed using independent sample t-tests, MANOVA, and SEM techniques.The results reveal that Indonesian students scored significantly higher across all dimensions of academic self-efficacy. For instance, the "Confidence in Mastery" dimension scored 75.34 for Indonesian students compared to 68.12 for Egyptian students (p < 0.01). In the "Academic Resilience" dimension, Indonesian students scored 69.88 versus 62.33 for their Egyptian counterparts (p < 0.01). Gender, socioeconomic status, and prior academic achievement emerged as significant demographic moderators. The study concludes that Indonesian students benefit from a supportive educational environment that fosters intellectual independence and resilience. These findings underscore the importance of culturally sensitive educational policies and interventions in enhancing students’ psychological well-being and academic success.